On the asymmetric effect of real exchange rate on growth: Evidence from Africa - James Temitope Dada (Economic Journal of Emerging Markets, 2022)
Purpose ― This study investigates the asymmetric effect of real exchange rates on the economic growth of twenty African countries for the period 2005 to 2019. Design/Method/Approach ― A refined method of Granger and Yoon (2002) was used to decompose real exchange into appreciation and depreciation. To address the problem of endogeneity and cross-sectional dependence, a two-steps system generalized method of moments, Driscoll-Kraay estimator, and Augmented Mean group were used. Findings ― This study established the presence of asymmetries in the real exchange rate in the region. Further, the study found that real exchange rate appreciation inhibits economic growth while real exchange rate depreciation is beneficial to growth in the region. The results are robust to different estimation techniques. Practical Implications ― The outcome of this study supports the traditional view of exchange rates on macroeconomic variables. Hence, findings from this study can help investors and policymakers in the region to better understand the dynamics of the exchange rate and its effect on economic growth. Originality/Value ― This study enriches the literature on the relationship between exchange rate and growth, especially in Africa using a refined approach to decompose exchange rate into appreciation and depreciation.